Impact of celebrity-endorsed environmental advertisements on green economy development - Li, Mengyu; Li, Jinglei; Yasin, Megat Al Imran; Hashim, Norliana; Ang, Lay Hoon; Bidin, Rosmiza (Elsevier, 2022)
This study offers a thorough analysis and evaluation of the impact of celebrity environmental advertisements on the development of green economy. According to our findings, celebrity-endorsed public service announcements (PSAs) tend to be more successful than non–celebrity-endorsed PSAs. This result is based on participant eye-movement data while viewing PSA images with and without celebrity endorsements. PSAs featuring celebrities received greater and longer gazes, and yielded a better re-recognition effect when compared with non-celebrity PSAs. In terms of time spent viewing, number of gazes, and recertification results, PSAs featuring host or anchor celebrities outperformed those featuring acting and sports celebrities. The process of sharing behavior on social media with regard to environmental PSAs takes place through self-exposure, assuming others' influence until the sharing behavior occurs. Perceived attitudes toward others' contact, the perceived social media experiences of others, and the perceived presence of social capital are the main factors of assumed influence regarding sharing behavior of environmental PSAs on social media. Our findings suggest that relevant media should focus on initiating, deepening, and sustaining sharing behavior with creative advertising, social contact, and social capital, respectively to improve the re-dissemination of environmental PSAs.